Cineclube no ensino médio: formação e protagonismo estudantil - Gomes, Thaisy de Carvalho Rocha (2023)
This dissertation presents Cineclube Goiany and its main contributions to high school students in a state public school in Goiás. The question that guided its creation was the following: how would a school film club collaborate in the formation and protagonism of high school students at Colégio Estadual Polivalente Professor Goiany Prates, in the city of Goiânia, Goiás? For this, an action research was carried out, based on the following authors: Freire (1996), Limeira (2015), Venturini and Medeiros (2018), Rizzo Junior (2011), Migliorin (2015), among others. The analysis approach was qualitative, with care to participate, monitor and record the process of creating and implementing the film club, through the appropriate image and audio authorizations, as well as presenting the production of short films and/or other audiovisual productions carried out by the students. participants. The commitment of the students to the realization of the film club, Cine Goiany, is observed, and they created their own channel on Youtube, a website and likewise held the Cine Goiany Short Film Festival, with the participation of the entire community school. It could be seen that the activities carried out by the film club related to the cinematographic/audiovisual language (film screenings, debates, training workshops, production of short films and festival) provide students with an autonomous, creative educational experience that is articulated with their social reality. They expanded their knowledge of the explored language, as well as shared and built knowledge.